Creon's ghost law, justice, and the humanities - Tomain, Joseph P., 1948- (Oxford : Oxford University Press, 2009)
This book pairs literary and philosophical stories from the humanities with various contemporary jurisprudential accounts of why morality should or should not enter into the theory and practice of the law, demonstrating how the humanities can illuminate our understanding of the law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Law and literature; Law in literature